DAMPAK ERUPSI MERAPI 2010 TERHADAP PEMANFAATAN LAHAN DAN DAYA PULIH MASYARAKAT DI KECAMATAN CANGKRINGAN - , ALVYNTHA GLAUDIA ARDIANINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gendol Watershed be a research location because this watershed is the most severely affected. Cangkringan was chosen as the focus area on this research because this area as one of the District in Sleman that located on the slopes of Mount Merapi and the resources was affected. The changing of land use after the eruption can changes the economic activity of the communities, particularly for agricultural. The aims of this research are: (1). Identify the impact of Merapi eruption in 2010 for land use changes, (2). Analyzing the impact of land use changes for economic activities (livelihood) on local community